Perilaku Hidup Bersih dan Sehat Mahasiswa PJKR 2019 Kelas C Universitas Singaperbangsa Karawang saat Pandemi Covid-19 - Rahmawati, Desi; Fathurrahaman, Iqbal (Universitas Singaperbangsa, 2022)
This research aims to analyze the level of clean and healthy living behavior of PJKR 19 class C students at Singaperbangsa University Karawang during the Covid-19 Pandemic. The method used in this research is a survey with a quantitative descriptive research type. The instruments used were questionnaires and data collection using the Google Form application. The research population was students from the Department of Physical Education, Health and Recreation class C class 2019. The sample was determined using purposive sampling. Based on the specified criteria, a sample with the number of students is generated. The data analysis technique uses percentages. The conclusion of this research states that the clean and healthy living behavior of students from the Department of Physical Education, Health and Recreation class C Singaperbangsa Karawang during the Covid-19 pandemic was in the very high category, there were 2 students (7.76%), in the high category there were 3 students (18.59% ), in the moderate category there were 13 students (29.65%), in the low category there were 4 students (20.94), and in the very low category there were 7 students (23.06%). The highest frequency was sufficient criteria with 13 students (29.65%).